Minimum wage conference, 1906 (1906)
1906 1880-1914 "Minimum wage conference, 1906" [EP0209], 1906 The National Anti-Sweating League was formed as a result of interest in the Exhibition of Sweated Industries organised by the Daily News in May 1906. In October 1906, the League organised this conference on establishing a legal minimum wage.